Unveiling the Excellent Leadership Qualities and Practices of Principals in Islamic Schools: A Systematic Literature Review - Saidah Mohd Said; Sabariah Sharif; Mohd Khairuddin Abdullah @Jerry Abdullah (International Journal of Learning, Teaching and Educational Research, 2023)
This systematic literature review (SLR) aimed to investigate leadership practices among Islamic school principals to determine their characteristics and influential factors. Guided by the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) approach, the study scrutinized 16 articles published between 2017 and 2022 sourced from three databases: Scopus, Dimensions, and Google Scholar. The findings unveil several themes, including instructional practices, leadership styles, good exemplars, relationship and engagement, ethical values, communication, flexibility, adaptability, and justice. These themes underscore the intricate nature of Islamic school leadership and its intersection with cultural and contextual factors. Intrinsic aspects, such as spirituality, attitude, and ability, and extrinsic components, such as organizational context and socio-religious influences, significantly mold principals’ practices. These insights echo previous research accentuating the role of attitudes, norms, and perceived behavioral control in shaping leadership behavior. The study emphasizes cultivating affirmative attitudes and cultural norms to foster inclusive and diverse environments. The implications underscore the need for multifaceted leadership strategies, adaptability, and ethical values. Future studies are recommended to incorporate quantitative methods and broaden the geographical scope for a comprehensive grasp of Islamic school leadership. Thus, this SLR advances insights into Islamic school leadership, facilitating effective practices across diverse educational settings.